USING LEXICON TRANSFORMATION IN THE TRANSLATION OF TOPONYMS - Barno Buranova (PhD) (Galaxy International Interdisciplinary Research Journal, 2022)
How similar original text in the turkmanishtranslation of toponyms, monuments, historical place and period in the novel of Pirimkul Kadirov “Starry nights” (“Yulduzlitunlar”), achievement and deficiency in describing the names of places, the methods of transcription and translation which was appeared while translation are analyzed in this article. Furthermore, it is given free definition of extra historical and geographic facts translating the names of places in the translation of toponyms using transcription and transliteration based on comparative-comparative components by the translator. Enriching the image and description of events in the passages related to toponyms, combining the geographical location of mountains, rivers, castles, cities and towns, villages with natural landscapes, as well as artistic painting in the image is also analyzed.